DAMPAK EKONOMI AKIBAT OUTBREAK PENYAKIT MULUT DAN KUKU PADA TERNAK SAPI DAN KERBAU DI INDONESIA - Achmad Firman; Iman Trisman; Rino Hadiwijaya Puradireja (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
Indonesia has been hit by outbreak of foot and mouth disease (FMD) after more than 30 years of being free of FMD. This study aimed to determine the level of transmission of the FMD virus and the potential economic losses due to the FMD outbreak. The method used in this research was a case study in which the data used for analysis was secondary data. The analytical method was used the reproduction number (R0) and the economic impact of FMD by using the Rushton and Knight formula. The results showed that the rate of transmission of the FMD virus was R0 = 2.85, i.e. one animal exposed to the FMD virus could infect three cattle for two weeks. The economic impact of the PMK outbreak is estimated at Rp 38.67 trillion. Therefore, the government must immediately vaccinate the affected cattle and buffalo to reduce the transmission rate.